RANCANGAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN PADA SNEAKERS KVLT SHOES CARE MENGGUNAKAN METODE SERVQUAL DAN QFD - Hani Musyaffa Hadi, (2021)
This research was conducted to analyze the quality of service provided by Micro, Small and Medium Enterprises (MSME) Sneakers KVLT to its customers. The purpose of this research is to obtain an effective service design for the company in its efforts to improve the quality of services that previously existed in MSMEs Sneakers KVLT. In this study, the analysis method used was the integration between Servqual (Service Quality) and QFD (Quality Function Deployment) method modeled into the form of House of Quality. Based on the results of this study, it is known that the integration between these two methods is effective enough to analyze the quality of services available in MSMEs Sneakers KVLT. In addition, from the integration of these two methods it is known that the service variables that should be prioritized to be improved and improved are reliability dimension variables and for its attributes are MSMEs Sneakers KVLT must be able to meet the Quality of Washing According to Standards. Besides that, through the integration of servqual and QFD method, the result that technical steps that need to be done and prioritized to improve and improve the quality of services in MSMEs Sneakers KVLT is by Providing Training to Employees.